Understanding the Apparently Poor Conductivity of Galvanized Steel Plates - Andrea Cozza (IEEE, 2021)
This paper investigates the physical reasons for the apparently poor conductivity of galvanized steel plates (GSP), which has not yet received a proper explanation. Apparent conductivities as low as 0.1 MS/m were reported in the past, which are incongruously low compared to the DC conductivity of steels (4 to 8 MS/m), or zinc (16.7 MS/m), the most common coating agent used against corrosion in steel products. A comprehensive review of results from metallurgy and materials science is presented, providing insights about the multi-layered structure of zinc-based coatings. These are found to be made of a limited set of intermetallic zinc-iron compounds each characterized by a steeply decreasing conductivity as their iron percentage increases. Depending on the galvanization process the relative thickness of these layers can vary widely, explaining the seemingly random apparent conductivity of GSP. Theoretical modeling of these structures shows that their apparent conductivity scales linearly with the frequency, suggesting that it can be far lower than acknowledged so far. An extensive analysis of power-dissipation data from the literature of GSP-based reverberation chambers confirms these predictions, with multiple instances of apparent conductivities as low as 10 kS/m. The conclusion is not that GSP are hopelessly poorly conductive, but rather that care should be taken in selecting the right coating technology, not only based on corrosion protection and minimizing costs, but also in view of its impact on GSP conductivity.